Parafunção severa: reabilitação oral com prótese total mandibular x overlay maxilar: relato de caso - Lara, Rafael Alves de [UNESP] (2012)
In many oral rehabilitation professionals seeking venture renew people smile. However, these procedures have functional implications and aesthetic criteria which must be satisfied so that the final result is predictable. The restoration of relations intermaxillary, phonetics, masticatory function, esthetics and patient comfort are the goals to be achieved. An effective way to achieve these goals when immediate reconstruction with permanent dentures is not possible, make use of a type of partial denture called overlay. Bruxism is a manifestation of biopsychological imbalance that affects the stomatognathic system, characterized by clenching and / or attrition of teeth together so centric or eccentric, can be manifestation of nocturnal or diurnal. Its effects can manifest themselves in different parts of the stomatognathic system, varying the severity of the damage as the resistance of the structures affected, the time of existence, its regularity and the general state of the wearer. The description of the steps followed in solving this case, in which the patient edentulous mandibular arch while the maxillary arch showed absence of teeth 16 and 26 and, except for the teeth 17 and 27, all other teeth showed wear very sharp in the sense denoting incisal cervical, severe impairment of the vertical dimension, the quality of masticatory function and a marked impairment phonetic, this case report aims to guide the beginning of a rehabilitation, as well as the transitional phase of treatment for recovery of functional and aesthetic relationships intermaxillary .